EDUKASI PENINGKATAN PENGETAHUAN MENGENAI PERILAKU HIDUP BERSIH DAN SEHAT PADA SISWA SMAN 16 PEKANBARU - Pratiwi, Yuharika; Anggraini, Susiana; Putri, Retno; Suryatra, Annisa Yolanda; Tulhusna, Widia (Kreativitas Pada Pengabdian Masyarakat (Krepa), 2023)
This service aims to increase knowledge about clean and healthy living behavior (PHBS) among students at SMAN 16 Pekanbaru. Knowledge of PHBS is very important to improve the health of individuals and society as a whole. Through an interactive and participatory approach, researchers and service assistants deliver material that focuses on the importance of personal hygiene, the environment and healthy eating patterns. The results of this service show a significant increase in students' knowledge regarding PHBS. They become more aware of the importance of keeping themselves and their surroundings clean. Apart from that, students also understand more about the positive impact of a healthy diet on physical and mental health. Apart from increasing knowledge, this service also has a long-term impact by encouraging students to become agents of change in their environment. They become more aware of their role in creating a clean and healthy school environment, and act as drivers of healthy living habits in their families and communities. With the awareness and knowledge gained from this service, it is hoped that SMAN 16 Pekanbaru students will be able to carry out clean and healthy living habits in a sustainable manner, as well as inspire others to do the same. This service is a positive first step in improving the quality of life for students and society as a whole.